Scoping review of clinical practice guidelines on the management of benign liver tumours. Issue 1 (6th August 2021) - Haring, Martijn P D; Cuperus, Frans J C; Duiker, Evelien W; de Haas, Robbert J; de Meijer, Vincent E
Abstract : Objective: Benign liver tumours (BLT) are increasingly diagnosed as incidentalomas. Clinical implications and management vary across and within the different types of BLT. High-quality clinical practice guidelines are needed, because of the many nuances in tumour types, diagnostic modalities, and conservative and invasive management strategies. Yet, available observational evidence is subject to interpretation which may lead to practice variation. Therefore, we aimed to systematically search for available clinical practice guidelines on BLT, to critically appraise them, and to compare management recommendations. Design: A scoping review was performed within MEDLINE, EMBASE, and Web of Science. All BLT guidelines published in peer-reviewed, and English language journals were eligible for inclusion. Clinical practice guidelines on BLT were analysed, compared, and critically appraised using the Appraisal of Guidelines, Research and Evaluation (AGREE II) checklist regarding hepatic haemangioma, focal nodular hyperplasia (FNH), and hepatocellular adenoma (HCA). Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations (PRISMA) for scoping reviews were adhered to. Results: The literature search yielded unique 367 papers, 348 were excluded after screening of title/abstract, and 16 after full-text screening. Three guidelines were included: the American College of Gastroenterology (ACG; 2014), Brazilian Society of Hepatology (SBH; 2015), and European Association for the Study of the Liver (EASL; 2016). There was no uniformity in the assessment methods for grading and gravity of recommendations between guidelines. Among observed differences were: (1) indications for biopsy in all three tumours; (2) advices on contraceptive pills and follow-up in FNH and HCA; (3) use of an individualised approach to HCA; (4) absence of recommendations for treatment of HCA in men; and (5) approaches to HCA subtype identification on magnetic resonance imaging. Conclusion: Recognising differences in recommendations can assist in harmonisation of practice standards and identify unmet needs in research. This may ultimately contribute to improved global patient care.